Morphological and molecular differentiation of lacewing species (Neuroptera: Chrysopidae) - CADENA, PATRICIA; ÁNGEL, FERNANDO; GÓMEZ, LUIS A.; GONZÁLEZ, RANULFO (Revista Colombiana de Entomología, 2007)
In the Cauca Valley (Colombia), the distribution and identification of the most abundant lacewing species were studied in zones where sugar cane (Saccharum spp.) is cultivated. It has therefore been possible to determine the species that could be used to counter the effect of the yellow aphid Sipha flava (Hemiptera: Aphididae) on the overall production of sugar cane. Although the lacewing species and morphotypes in the current study can be separated using morphological characters, the validity of those characters was studied. To do that, we established a morphological differentiation using internal genitalia and a molecular differentiation using a PCR-RFLP analysis of the 18S rDNA region of 11 species from three genera of the family Chrysopidae (Ceraeochrysa, Chrysoperla, and Leucochrysa), some of whom could be important biological control agents of the yellow sugar cane aphid S. flava. The characters used proved to be useful for distinguishing the species. In the case of internal genitalia, there were different patterns of the structures. In the case of molecular data, the species were differentiated using only one combination of NS primers for the DNA amplification, followed by digestion of fragments with a restriction enzyme (NS5-NS6+DraI). These results add to the taxonomic understanding of the family, and may help resolve systematic problems within the genera.